2021
DOI: 10.3390/molecules26206168
|View full text |Cite
|
Sign up to set email alerts
|

Shedding Light on the Pharmacological Interactions between μ-Opioid Analgesics and Angiotensin Receptor Modulators: A New Option for Treating Chronic Pain

Abstract: The current protocols for neuropathic pain management include µ-opioid receptor (MOR) analgesics alongside other drugs; however, there is debate on the effectiveness of opioids. Nevertheless, dose escalation is required to maintain their analgesia, which, in turn, contributes to a further increase in opioid side effects. Finding novel approaches to effectively control chronic pain, particularly neuropathic pain, is a great challenge clinically. Literature data related to pain transmission reveal that angiotens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 151 publications
0
6
0
Order By: Relevance
“…The role of angiotensin receptors and ligands in the central nervous system (CNS) and their possible therapeutic use in the alleviation of NP, among other pain types, are emerging as an important area of pain research. Other groups and we ourselves have reported on the connection between the RAS and NP [5,21,22] and possible pharmacological interactions between the opioid and angiotensin systems regarding analgesia [23]. In the present work, we provide, to the best of our knowledge, the first evidence for enhanced analgesia following co-administration of a clinically, widely used, angiotensin receptor blocker (ARB) and morphine in a neuropathic rodent model.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…The role of angiotensin receptors and ligands in the central nervous system (CNS) and their possible therapeutic use in the alleviation of NP, among other pain types, are emerging as an important area of pain research. Other groups and we ourselves have reported on the connection between the RAS and NP [5,21,22] and possible pharmacological interactions between the opioid and angiotensin systems regarding analgesia [23]. In the present work, we provide, to the best of our knowledge, the first evidence for enhanced analgesia following co-administration of a clinically, widely used, angiotensin receptor blocker (ARB) and morphine in a neuropathic rodent model.…”
Section: Introductionmentioning
confidence: 58%
“…Therefore, the need to develop novel drugs or new approaches encourages researchers to continue working in this field. In the last decades, many promising drug targets have been identified as potential therapeutic targets for future neuropathic pain treatment, such as angiotensin receptor type 1 [22,23]. The use of combination treatment regimens has also been considered in order to increase the effectiveness without increasing the undesirable effects of the elements of the combination.…”
Section: Discussionmentioning
confidence: 99%
“…29 Accumulating evidence moreover suggests that central angiotensin inhibition modulates reward processing, reciprocal social interaction and pain processing via interactions with the opioid system. 30,31 The role of the AT1R in stimulating vasopressin 32 release may additionally mediate effects on anxiety during unpredictable threats 33 (for the anxiolytic potential of vasopressin in humans see Zhuang et al, 2021). 34 Together these studies describe further biological pathways that may mediate the complex effects of the AT1R, however, how these systems interact with the central AT1R system to regulate complex human behaviors has not been systematically examined.…”
Section: Introductionmentioning
confidence: 99%
“…Three articles in this Special Issue explore dimerization and intracellular interactions and positive or negative cooperativity between the µOR and angiotensin (AT2) receptors [ 30 ], serotonin (5HT 1A ) receptor [ 31 ], and free fatty acid (FFA) receptors [ 32 ]. Kiraly et al reviewed positive cooperativity between µOR analgesics and angiotensin receptor inhibition [ 30 ].…”
mentioning
confidence: 99%
“…Three articles in this Special Issue explore dimerization and intracellular interactions and positive or negative cooperativity between the µOR and angiotensin (AT2) receptors [ 30 ], serotonin (5HT 1A ) receptor [ 31 ], and free fatty acid (FFA) receptors [ 32 ]. Kiraly et al reviewed positive cooperativity between µOR analgesics and angiotensin receptor inhibition [ 30 ]. The premise of the review is based on studies, for example, that found angiotensin-converting enzyme inhibition enhancing morphine antinociception and reducing opioid antinociceptive tolerance [ 33 ] and that the activation of angiotensin AT2 receptor decreases morphine antinociception [ 34 ].…”
mentioning
confidence: 99%